New Countries Applying the Harmonized System Nomenclature: Update 2014 - Carsten Weerth (Global Trade and Customs Journal, 2014)
More countries and economic regions are applying the Harmonized Commodity Description and Coding System (Harmonized System Convention). Here is an overview for 2014 of the new countries which are using the worldwide uniform language of trade now and will apply the tariff scheme from 2015.
Additional information: Pre-Print proofs according to the Romeo/Sherpa Policy of this yellow journal.
Keywords: F53; K33; K34; 330; Customs Law; Customs Classification; World Customs Organization; Tariff Classification; Trade Facilitation; Harmonized System